The Implementation of a Computational Thinking-Based Method to Facilitate German Language Learning for 11th Grade Students of SMAN 6 Malang - Malta Juvike Ohenokha; Deddy Kurniawan (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2025)
This study aims to identify students’ activities and responses to the implementation of a Computational Thinking-based method in German language learning for 11th grade students at SMAN 6 Malang. The research method used is descriptive qualitative, with data sources consisting of teaching and learning activities, 23 students, and a German language teacher. Data were collected through observation and interviews to describe students’ engagement and their responses to the learning process. The observation results show that students became more active, enthusiastic, and involved in the learning, particularly in speaking skills. The interviews supported these findings, indicating that students felt they understood and remembered the material better and were more interested in learning new things through this method. The integration of findings from both data sources shows that the implementation of the Computational Thinking-based method can promote students’ interest, understanding, and learning experience. Despite some limitations, such as short duration and the need for varied activities, this method helps create an active, enjoyable, and meaningful German learning environment.